Comparison of the pre-treatment testosterone levels in benign prostatic hyperplasia and prostate cancer patients - D.E. Orakwe; K.H. Tijani; E.A. Jeje; M.A. Ogunjimi; R.W. Ojewola (African Journal of Urology, 2017)
Objectives: To compare serum testosterone and prostate specific antigen (PSA) levels of patients diagnosed of prostate cancer to those with benign prostatic hyperplasia (BPH). Subjects and methods: One hundred and thirteen male patients with or without LUTS who had indication(s) for prostate biopsies were recruited. Blood samples were analysed for serum testosterone and serum PSA. Prostate sizes were measured and PSA densities calculated before trans-rectal prostate biopsies were performed. Results: On histology of prostate biopsy specimens, 54 patients (47.8%) had prostate adenocarcinoma while 59 patients (52.2%) had BPH. Serum testosterone levels were lower in the prostate cancer group (23.09 ± 2.31 nmol/L versus 24.37 ± 1.94 nmol/L in the BPH group) but this difference was not statistically significant (p = 0.671). Serum testosterone also did not differ significantly with Gleason grade and Gleason score in patients with prostate cancer. Serum PSA and PSA density (PSAD) values were significantly higher in men with prostate cancer, and also in prostate cancer patients with high grade disease. Conclusion: Serum testosterone levels of patients with prostate cancer did not significantly differ from those of patients with BPH and were not related to grade in prostate cancer patients.